Reapropiación de recursos educativos obsoletos ante las brechas tecnológicas durante el Covid-19 - Pérez-Pinzón, Luis Rubén; Correa, Gladys (Educación y Ciudad, 2023)
The printed, mechanical and audiovisual educational resources that had been questioned and considered traditional in the face of the connectivist paradigm were reestablished and strengthened during the covid-19 pandemic, as well as becoming alternatives for educational improvement in the face of limitations in connectivity in suburban areas. rural and wild. The communication of the reflection article is to describe the international trends in the use of non-digital remote technologies in the global context, as well as the experiences of adaptation in Colombia and Panama. The result of a doctoral thesis in educational technology, the qualitative approach and interpretive method research reviews and contrasts the experiences in the use of non-digital remote educational resources, in different international contexts. In conclusion, the technological gaps in the most remote areas without connectivity led during the pandemic to the promotion and massive reappropriation of obsolete educational resources.